Hubungan Taste Abnormalities Dan Durasi Tidur Dengan Overweight Pada Mahasiswa Dan Mahasiswi: The Relationship Between Taste Abnormalities and Sleep Duration with Overweight in Male and Female Students - Safitri, Dina; Susaldi, Susaldi (Indonesian Scholar Journal of Nursing and Midwifery Science, 2025)
Introduction: Overweight is defined as the accumulation of abnormal or excess fat that occurs due to an imbalance in energy intake with energy expenditure over a long period of time. decreased sensitivity to sweet tastes then humans will tend to consume more sugar and if not balanced with a balanced diet, they are at risk of developing diabetes mellitus, obesity, accelerating aging and causing cavities. Factors that affect sleep quality in adolescents include ethnicity, religion, location of home, parents' alcohol drinking status, satisfaction with academic performance, smoking, relationships with friends, internet use before bed. Overweight and obesity among university students have become a growing public health concern, influenced by various lifestyle and biological factors. Taste abnormalities, including changes in taste sensitivity or preference, may alter food intake patterns, leading to increased caloric consumption. Additionally, sleep duration has been identified as a critical determinant of body weight regulation where insufficient sleep can disrupt hormonal balance and appetite control.  Methods: the research used in this study is quantitative using an observational approach. The research design used is cross-sectional. The population in this study were 96 regular undergraduate students of Nursing at the University of Indonesia Maju in Jakarta. The researcher used the chi-square test with a confidence level of 95% or a significance level of 5%. This cross-sectional study involved a sample of male and female students selected using a stratified random sampling technique. Data were collected through a structured questionnaire that assessed demographic characteristics, sleep duration and self-reported taste perception abnormalities. Body mass index (BMI) was calculated based on measured height and weight to determine overweight status. Statistical analysis was conducted using chi-square and logistic regression tests to examine the relationship between taste abnormalities, sleep duration and overweight status. Results: Based on the results of the study, the p-value = 0.000 means p-value <α (0.05). The findings revealed a significant association between taste abnormalities and overweight (p < 0.05), where students experiencing taste sensitivity changes were more likely to be overweight compared to those with normal taste perception. Moreover, shorter sleep duration (< 7 hours per night) was significantly related to higher BMI levels (p < 0.01). Female students showed a higher prevalence of overweight compared to male students. Discussion: There is a relationship between Taste Abnormalities and Sleep Duration on Obesity of Students at the University of Indonesia Maju 2024. The results suggest that altered taste perception and inadequate sleep duration may play a considerable role in the development of overweight among university students. Taste abnormalities could influence dietary preferences toward high-fat or high-sugar foods, while reduced sleep duration may disrupt metabolic and hormonal pathways regulating hunger and satiety. Interventions promoting healthy sleep patterns and awareness of sensory health may be essential strategies to prevent overweight and obesity in young adults.